Financial Literacy as Household Capability: Its Role in Strengthening Marital Stability in Emerging Indonesian Families - Yogi Yogi; Ahmad Dakhoir (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Marital stability is increasingly influenced by couples’ ability to manage household finances effectively, yet empirical studies linking financial literacy to marital stability remain limited, particularly in developing country contexts. This study aims to analyse the role of family financial literacy as a life skill in strengthening marital stability among married couples in Central Kalimantan Province, Indonesia. The research employs a mixed-methods, sequential, explanatory design integrating quantitative and qualitative approaches. Quantitative data were collected through a survey of 150 married couples (N = 150) who participated in a family financial literacy education program using a pre–post-test design. Data were analysed using paired-samples t-tests, Pearson's correlation, and Structural Equation Modeling (SEM) to examine the structural relationship between financial literacy and marital stability. Qualitative data were obtained through in-depth interviews to explore couples’ experiences in managing household finances. The results show a significant increase in financial literacy scores after the educational intervention. Statistical analysis indicates a strong positive relationship between financial literacy and marital stability (r = 0.657, p < 0.01), with financial literacy explaining 43.1% of the variance in marital stability. Qualitative findings reveal that improved financial literacy encourages better financial communication, joint decision-making, and reduced financial conflict within households. This study demonstrates that family financial literacy is a critical life skill that strengthens marital stability by improving financial behaviour and communication between spouses, highlighting the importance of integrating financial literacy into premarital education and family empowerment programs.